Supply Chain Efficiency and Its Impact on the Income of Oil Palm Farmers in Terawas Village, Musi Rawas Regency, South Sumatra Province - Febrina Nur Annisa; Widya Analisa (Jurusan Budidaya Perkebunan, 2026)
Oil palm is a strategic commodity in Indonesia, contributing significantly to rural income and regional economic development. However, inefficiencies in the supply chain, particularly at the village level, often reduce the economic benefits farmers receive. This study aims to analyze the supply chain structure and the effect of marketing channels on the income of oil palm farmers in Terawas Village, Musi Rawas Regency. This study employed a quantitative descriptive approach, using a survey, with a purposive sample of 60 farmers. Data were collected from primary and secondary sources and analyzed using descriptive methods, combined with marketing margins, farmers’ shares, and benefit-cost ratio (R/C) models. This study offers novelty by providing empirical evidence at the village level that integrates multiple efficiency indicators simultaneously, a feature that remains limited in previous research. The results show three main marketing channels: farmers–middlemen–palm oil mills, farmers–collectors–palm oil mills, and farmers–direct to mills. Shorter marketing channels are more efficient and generate higher income for farmers. The highest marketing margin occurs in the longest channel (Rp700/Kg), while the lowest is in the direct channel (Rp400/Kg). The highest farmer’s share is found in the direct channel (84%), compared to 72% in the middlemen channel. The R/C ratio indicates that all channels are profitable, with the highest efficiency in the direct channel (1.75). This study recommends strengthening farmer institutions, improving access to market information, and promoting direct marketing channels to reduce dependency on intermediaries and enhance supply chain efficiency.